1985
DOI: 10.1002/tea.3660220507
|View full text |Cite
|
Sign up to set email alerts
|

Student understanding of chemical equation balancing

Abstract: Fourteen high school chemistry students from two different schools were interviewed in depth on how they balanced simple chemical equations, the knowledge they employed while balancing the equations, and their representation of the balanced equations with diagrams. The equations were of the type employed when students are first introduced to chemical equation balancing in high school. All students were able to successfully balance the four equations presented to them. However, seven of the twelve students were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
22

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 12 publications
5
91
0
22
Order By: Relevance
“…They interpreted an equation, such as C(s) + O 2 (g) → CO 2 (g), as a composition of letters, numbers, and lines instead of a process of bond formation and breaking. The technique of balancing chemical equations made students picture chemical equations as mathematical puzzles (Ben-Zvi, Eylon, & Silberstein, 1987), and they could even work algorithms without having a conceptual understanding of the phenomena (Nakhleh, 1993;Yarroch, 1985). Thus, while chemists view a chemical reaction represented by an equation as an interactive and dynamics process, students can only construct a static model of it.…”
Section: Difficulties In Comprehending and Interpreting Representationsmentioning
confidence: 99%
“…They interpreted an equation, such as C(s) + O 2 (g) → CO 2 (g), as a composition of letters, numbers, and lines instead of a process of bond formation and breaking. The technique of balancing chemical equations made students picture chemical equations as mathematical puzzles (Ben-Zvi, Eylon, & Silberstein, 1987), and they could even work algorithms without having a conceptual understanding of the phenomena (Nakhleh, 1993;Yarroch, 1985). Thus, while chemists view a chemical reaction represented by an equation as an interactive and dynamics process, students can only construct a static model of it.…”
Section: Difficulties In Comprehending and Interpreting Representationsmentioning
confidence: 99%
“…Equally important, students need to master certain abilities and skills such as visualizing a chemical reaction at the molecular level, reasoning about a macroscopic phenomenon using chemical representations, and coordinating multiple representations (Ben-Zvi, Eylon, & Silberstein, 1987;Gabel & Samuel, 1987;Hesse & Anderson, 1992;Kozma, 2000Kozma, , 2003Krajcik, 1991;Yarroch, 1985). Finally, students need to develop a coherent conceptual framework that integrates their knowledge and skills to establish a scientiÞc theory of the entities and processes that underlie a given observed phenomenon (Kozma, Russell, Jones, Marx, & Davis, 1996;Russell et al, 1997).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…[25][26][27][28] For instance, students who can successfully balance chemical equations often do not understand the relationship to the particulate or molecular level. 28 Even when students are given diagrams representing molecules before and after a reaction, they have difficulty describing the reaction and writing an equation. 26 In another study, Ben-Zvi et al observed that students held a static view of reactions and lacked an understanding of the dynamic nature where bonds break, atoms rearrange, and new bonds form.…”
Section: Chemical Reactionsmentioning
confidence: 99%